An Adsorption-Catalysis Pathway toward Sustainable Application of Mesoporous Carbon Nanospheres for Efficient Environmental Remediation - Azhar, M.R.; Arafat, Y.; Zhong, Yijun; Khiadani, M.; Tade, Moses; Wang, Shaobin; Shao, Zongping (2021)
Large-surface area carbon materials have attracted a great deal of attention recently due to their promising applications in adsorption, energy storage, and catalysis. In this study, a green and sustainable wastewater treatment strategy, involving pre-adsorption of mesoporous carbon nanospheres (MCNS) with water contaminants and subsequent advanced oxidation of pre-adsorbed molecules and an additional water contaminant, is studied for the treatment of wastewater and regeneration of MCNS simultaneously. Here, MCNS were facilely synthesized, which demonstrated high efficiency in adsorptive removal of neutral, cationic, and anionic organic water contaminants. MCNS with pre-adsorbed contaminant molecules were found to be highly active catalysts for the peroxymonosulfate (PMS)-activated removal of phenol in wastewater. Meanwhile, the pre-adsorbed organic contaminants in MCNS were also removed by PMS, leading to a re-cleaned surface for subsequent adsorptive removal of the water contaminant. Various parameters in adsorption and catalytic degradation were studied to elucidate the performance of MCNS as well as the adsorption and degradation mechanism. The recyclability of MCNS for multiple adsorption-catalysis runs makes the process green, sustainable, and cost-effective without introducing any secondary contaminants.